(untitled) (Fiep Bulletin - online, 2013)
The mobilization and use of endogenous substrates during exercise are important for energetic metabolism and athletic performance. In T2D, the better exercise intensity that should be used for training and fatty oxidation remains controversial. The aim of our study was to investigate the effects of progressive exercise protocol in T2D patient, carried out at the percentage of the lipid and carbohydrate contribution to muscle energy in different intensities by indirect calorimetry. The transversal clinical case was performed with T2D male patient with age (years): 59; height (cm): 173; weight (kg): 101.2; body mass index (BMI, kgm-2): 33.81; fasting blood glucose (mmol L-1): 8.8. This patient is poorly active and not engaged in any other training programs. The results suggest the exercise prescription in intensives between 45-50% of VO (8,5 mL/kg/min) to 2peak optimized Fatty consumption on T2D patient.